Comparing Single vs. Combined Cerebrospinal Fluid Parameters for Diagnosing Full-Term Neonatal Bacterial Meningitis - Huang, Heyu; Tan, Jintong; Gong, Xiaohui; Li, Jing; Wang, Liping; Xu, Min; Zhang, Xi; Zhang, Yongjun; Huang, Lisu (Frontiers in Neurology, 2019)
Objectives: To find the best diagnostic cutoff values of single and suitable combination of cerebrospinal fluid (CSF) parameters and compare their efficacies in term neonatal bacterial meningitis diagnosis. Study design: The retrospective part of Shanghai Neonate Meningitis Cohort included all term neonates who underwent lumbar puncture from 2000 to 2017. Those with severe neurological diseases, ventricular drainage history, or traumatic lumbar puncture were excluded. Reference ranges were determined for non-bacterial meningitis neonates by using the 5th, 25th, 50th, 75th, and 95th quartiles for CSF parameters, and their relationships to age were calculated using generalized additive models testing for liner relationships. The best cutoff values of single parameters were calculated by receiver operating characteristic (ROC) analyses and Youden’s index, and parameters with good diagnostic efficacies were included into combined parameters by logistic regression. The diagnostic efficacies of single and combined parameters were compared in bacterial meningitis neonates. Results: White blood cells (WBCs) in CSF had better diagnostic efficacy than protein, glucose, lactic dehydrogenase, and chloride. The sensitivity and specificity of WBCs cutoff values (20×106/L) for diagnosing neonatal bacterial meningitis were 95.1% and 98.7%, respectively. Different combined parameters improved specificities slightly, ranging from 99.0% to 99.7%, but sensitivities were barely unchanged, ranging from 95.1% to 96.0%. Conclusions: Combined parameters improve the sensitivity and specificity of diagnosis slightly compared to CSF WBC alone.